HEALTH EDUCATION ABOUT STUNTING AT THE AMANAH MEKAR SERUMPUN COMMUNITY HEALTH CENTER - Hastuti Marlina; Sherly Vermita Warlenda (Jurnal Pengabdian Kolaborasi dan Inovasi IPTEKS, 2026)
Stunting is a chronic nutritional problem that significantly impacts human capital, necessitating integrated interventions at the grassroots level, such as in the Amanah Mekar Serumpun Community Health Center (Puskesmas). This topic was chosen based on the urgency of improving public health literacy and strengthening the role of cadres and health workers in early detection of toddler growth to reduce regional stunting prevalence. This community service activity employed a pre-experimental design with a One-Group Pretest-Posttest Design, combined with interactive health education, processing of local foods rich in animal protein, and quantitative evaluation using structured questionnaires and gain score analysis with 30 participants. The implementation evaluation demonstrated that this discovery-based educational intervention significantly improved mothers' cognitive capacity and cadres' psychomotor skills in independently conducting anthropometric measurements according to standard operating procedures. Overall, this program proved effective in increasing family nutrition awareness and addressing barriers to nutritional adaptation at the household level. However, the limited duration of the intervention underscores the need for follow-up development programs, including digital-based village nutrition clinic models, to ensure continuous and real-time monitoring of toddler growth.